A side-sensitive synthetic chart combined with a VSS X¯ chart - Costa, Antonio F.B. [UNESP]; Machado, Marcela A.G. [UNESP] (Elsevier, 2016)
In independent investigations, the variable sample size (VSS) scheme and the side-sensitive synthetic (SS) rule proved to reduce the delay with which the X¯ chart signals. Based on these findings we investigate the X¯ chart's performance with the joint use of the VSS scheme and the side-sensitive synthetic rule. The SSVSS X¯ chart outperforms the pure VSS X¯ chart, especially when the risk of false alarms and the rate of inspected items per sampling cannot be high. In these cases, the VSS X¯ chart detects moderate mean shifts (around one standard deviation) in half of the time thanks to the side-sensitive synthetic rule.
Keywords: Quality control; Side-sensitive; Synthetic; VSS; X¯ chart